Impact of covid-19 toward Malaysia economy - Lau, Pea Chun; Lau, Zheng Kang; Lian, Khai Zhen; Li, Xin Ru (2022)
In this research study, we have gone through our investigation on the impact of Covid-19 towards Malaysia economy. The effects of Covid-19 have been disastrous for the world economy. It has been the latest global risk to disrupt Malaysia’s GDP growth rate. According to DOSM, since Malaysia went through the pandemic, the country's GDP index has dropped significantly from 2019 to 2020, from 4.3% to -5.6%. Some economic indicators such as exchange rate, inflation rate, and interest rate were also impacted severely during the Covid-19 pandemic. Thus, we would like to examine the relationship between exchange rate, inflation rate, interest rate with GDP growth rate of Malaysia during Covid-19 pandemic. We have applied ARDL model together with unit root test, CUSUM test, heteroskedasticity test, autocorrelation test, multicollinearity test and normality test by having sample period from January 2020 to March 2022 which included 27 observations. Throughout the findings, we discovered that there exists negative relationship among the exchange rate, inflation rate, interest rate with GDP growth rate of Malaysia in the long run. By having this finding, we hope that it may assist future researchers with some information about the impact of covid-19 on Malaysia’s economy. Additionally, policymakers and investors could have a study report for references in order to help them to make decision making to prevent uncertainty. Although this study has faced the limitation of lacking a data sample period, other researchers may be able to observe more sample periods which will be more accurate in the future as time goes by. We encourage future researchers to have comparisons of past, present and post Covid-19 pandemics and cover more variables in order to detect the impacts more obviously as references for policy implications in future.